PENINGKATAN KEMAMPUAN MANAJERIAL GURU MELALUI OPTIMALISASI PENGELOLAAN KELAS - Siti Zulaikha (Perspektif Ilmu Pendidikan, 2011)
A study towards teachers in the area of Bogor municipality is done on the premise that teachers should have some competence that can support their success in carrying out assigned tasks. One of the competence is a must have managerial competency, which is a competency that necessary mainly because teachers hold two different tasks and they are a central issue, namely the task of teaching and task of classroom management. The classroom management is one aspect of managerial competence of teachers which is very important in order to master the learning process. The failure of teacher in achieving the goal of learning is directly proportional to the inability of teachers in managing classes. In this study, data uncovered that managerial skills of teachers can be improved through teacher’s skills in managing the classroom.